2012
DOI: 10.1002/pmic.201100619
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the lungs of mice infected with different pathotypes of H5N1 avian influenza viruses

Abstract: The virulence of influenza virus is determined by viral and host factors. Data on the genetic basis of the virulence of H5N1 influenza viruses have increased over the past decade; however, the contributions of host factors to the outcomes of H5N1 infection remain largely unknown. Here, we tested two chicken H5N1 viruses in mice and found that A/chicken/VN1214/2007 was nonlethal in mice and only replicated in the lung, whereas A/chicken/VN1180/2006 was highly lethal and replicated systemically in mice. To inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 70 publications
(91 reference statements)
1
16
0
Order By: Relevance
“…By using two HPAI H5N1 viruses (CK/1180 and CK/1214) with similar genomes but different pathogenicities in mice (31, 32), in this study, we demonstrated that a single amino acid mutation at position 158 of the HA protein had fundamental effect on the systemic replication and pathogenicity of these H5N1 influenza viruses in mice. We further found that the substitution G158N introduced an N-linked glycosylation at positions 158 to 160 of the HA protein and that this N-linked glycosylation enhanced viral productivity in infected mammalian cells and exacerbated host immune and inflammatory responses to viral infection.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…By using two HPAI H5N1 viruses (CK/1180 and CK/1214) with similar genomes but different pathogenicities in mice (31, 32), in this study, we demonstrated that a single amino acid mutation at position 158 of the HA protein had fundamental effect on the systemic replication and pathogenicity of these H5N1 influenza viruses in mice. We further found that the substitution G158N introduced an N-linked glycosylation at positions 158 to 160 of the HA protein and that this N-linked glycosylation enhanced viral productivity in infected mammalian cells and exacerbated host immune and inflammatory responses to viral infection.…”
Section: Discussionmentioning
confidence: 64%
“…In our previous studies (31, 32), we characterized the pathogenicity and viral replication of CK/1180 and CK/1214 in mice and found that CK/1180 systemically replicated and showed high pathogenicity in mice, with a 50% mouse lethal dose (MLD 50 ) of 2.5 log 10 50% egg infectious doses (EID 50 ), but CK/1214 replicated only in lung tissue and displayed low virulence in mice. In this study, we found that even 10 7 EID 50 of CK/1214 did not kill mice (MLD 50 > 7.5 log 10 EID 50 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced chemiluminescence (ECL) anti-mouse IgG horseradish peroxidase-linked whole antibody (from sheep) was purchased from GE Healthcare. Western blotting was performed as described previously (16). Briefly, the samples were lysed with 2ϫ SDS loading buffer (Invitrogen) and subjected to SDS-polyacrylamide gel electrophoresis (SDS-PAGE).…”
Section: Cellsmentioning
confidence: 99%
“…Some proteomic analyses had been performed against influenza virus-host models, however, these studies on host response to influenza virus infection primarily targeted human influenza viruses, specifically, only one infection period. For instance, quantitative proteomics has been applied to influenza-host interactions in cells10111213 and several proteomic studies have also been carried out in influenza virus infected animals1415.…”
mentioning
confidence: 99%